Repetitive Transcranial Magnetic Stimulation in a Group of Treament-Resistant Obsessive-Compulsive Disorder Patients: A Descriptive Study - Topcuoğlu, Müge; Cinemre, Buket; Erdoğan, Ali; Nabiyeva, Naila (Acta Medica, 2022)
Objective: This study aims to investigate the effects of repetitive transcranial magnetic stimulation (rTMS) treatment in a group of treatment-resistant obsessive-compulsive disorder (OCD) patients and to examine the relationship between various sociodemographic and clinical variables and treatment response. Materials and Methods: Data including The Yale–Brown Obsessive Compulsive Scale (Y-BOCS) scores and various clinical and sociodemographic characteristics of 27 treatment-resistant OCD patients who received 30 sessions of low-frequency rTMS (LF-rTMS) treatment on the left dorsolateral prefrontal cortex (DLPFC) were analyzed. Results: Mean Y-BOCS scores decreased significantly across week 0 and the 3rd week (t(26)=10.59, p<.001) and continued to decrease significantly across weeks 3 and 6 (t(26)=11.47, p<.001). 21(78%) patients were responders with at least a %25 decrease in the mean Y-BOCS scores, and 10(47.6%) of these 21 patients also met the complete response criteria with a 35% or more reduction in Y-BOCS. No significant difference was observed between responders and non-responders regarding various clinical and sociodemographic variables. The only reported side effects were headaches and local scalp tenderness, which improved in a short time. Conclusion: This descriptive study has demonstrated the efficacy of a long-duration LF-rTMS application on the DLPFC in a group of drug-resistant OCD patients. This finding might contribute to the available literature, especially in drawing out a standardized treatment protocol in these cases.